INTEGRASI MEDIA STEM–AR DALAM PEMBELAJARAN MATERI LAPISAN BUMI PADA SISWA SEKOLAH DASAR - Yulianto, Iqbal; Arifatun, Lulu’; Eka Titi Anadaryani; Sri Sumartiningsih; Philip X. Fuchs (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of a Science, Technology, Engineering, and Mathematics–Augmented Reality (STEM–AR)–based learning media on the topic of Earth’s layers for fifth-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The participants were fifth-grade students of SDN Miroto Semarang Tengah. Data were collected through expert validation, student response questionnaires, and pretest–posttest assessments, and were analyzed using descriptive quantitative and qualitative methods. The results of expert validation indicated that the developed STEM–AR learning media met the criteria of high feasibility in terms of content accuracy, visual design, and interactivity. The limited trial results showed positive student responses, indicating a high level of practicality and ease of use. Furthermore, the effectiveness analysis revealed an improvement in students’ learning outcomes, as evidenced by an increase in the average score from 62.00 in the pretest to 84.00 in the posttest. These findings suggest that the integration of augmented reality with a STEM approach facilitates students’ understanding of abstract Earth science concepts through interactive three-dimensional visualization and integrated learning activities. Therefore, the STEM–AR learning media is considered feasible, practical, and effective, and has the potential to serve as an innovative instructional tool to enhance scientific literacy and student engagement in elementary science learning.